Ten Criteria for an Ideal Teacher to Memorize the Quran - Engkizar Engkizar; Azhar Jaafar; Hanifa Muslim; Ilham Mulyadi; Yandri Agusta Putra (Journal of Theory and Research Memorization Quran, 2025)
The phenomenology of Quran memorization is increasingly found among Muslim communities, both from children to the elderly. Of course, the success of a person in memorizing the Quran is inseparable from the guidance of a teacher, obviously the teacher in question has certain criteria that make the teacher an idol or ideal for a student. Precisely, this study aims to identify and analyze how the criteria for ideal teachers according to the assessment of students. This research uses qualitative methods with ethnography type. Data sources were taken through in-depth interviews with thirty informants selected using the purposive sampling technique, consisting of students and lecturers at one of the Quranic universities in Indonesia. All data were analyzed using Miles and Huberman's interactive technique. The research findings found ten criteria for ideal teachers from the perspective of students as mentors in memorizing the Quran. The ten criteria are i) providing motivation, ii) guiding students, iii) having deep knowledge, iv) patient, v) friendly, vi) firm, vii) mutqin “strong memorization” viii) discipline, ix) having Quranic art skills, x) giving rewards. The ten teacher criteria in this finding can be used as a reference for all Quranic education institutions in choosing Quranic teachers, because teachers with such criteria have succeeded in leading students to successfully memorize the Quran.